Introduction to Sociological Practice - Marshall, James (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
COURSE DESCRIPTION: This course introduces the practice of sociology in various social settings. Emphasis is placed on understanding how sociology may be applied to analyze and change situations in social reality. A recognition of the professions associated with sociology is also developed. This course is a prerequisite course for sociology majors with an emphasis in applied.